Tahap Perkembangan Moral Kohlberg pada Mahasiswa Usia Awal Dewasa. Studi Kasus pada Mahasiswa Prodi PGSD Universitas Nusa Putra Sukabumi: Kohlberg’s Stages of Moral Development in Early-Adulthood University Students: A Case Study of PGSD Students at Universitas Nusa Putra Sukabumi - Sukmawati, Wati Solihat (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
This study examines the relevance of Kohlberg’s stages of moral development among early-adulthood students enrolled in the Primary School Teacher Education (PGSD) program at Universitas Nusa Putra Sukabumi. The research aims to map the dominant stages of students’ moral reasoning, explore contextual factors influencing their moral decisions, and assess the applicability of Kohlberg’s assumptions in a local Indonesian context. Using a qualitative case study approach, six students were selected purposively and engaged through in-depth interviews based on three contextual moral dilemmas, supported by limited participant observation and document analysis. Findings indicate that most students operate within the conventional level, especially Stage 4, with occasional shifts toward Stage 5 in organizational dilemmas and regressions to Stage 2 under peer pressure. Moral reasoning was found to be unstable across contexts and strongly shaped by institutional norms, family values, and organizational experiences. These results suggest that Kohlberg’s model remains relevant but requires contextual adaptation, as moral reasoning among students is plural, situational, and influenced by social environments. The study highlights the need for enhanced ethical training, reflective practice, and structured professional development to strengthen moral reasoning competencies among prospective primary school teachers.